Fernand Pouillon, le double exilé de la politique du logement - Cécile Regnault; Luc Bousquet (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Fernand Pouillon (1912-1986) was a prominent figure in French architecture during the 20th century. HE was exiled twice throughout his life. First, when he left France for Algeria from 1965 and 1966 after his being put on trial for his involvement in the Comptoir national du logement. Then again two decades later in 1984, when he was hunted down by the Algerian government in somewhat of the same vigour which had welcomed him. His second exile led him back to Belcastel, where he stayed until his death in 1986. The paper examines the conditions of his two successive exiles, tracing the parallels between the reasoning that prevailed on both sides of the Mediterranean Sea. It sheds particular light on the second exile, which was less documented and much less mediatized than the first.